Penyuluhan Bahaya Narkoba serta Upaya Pencegahannya di Kalangan Remaja Kepada Siswa SMK 2 Wisata Perintis, Kota Depok. - Shabrina, Yusfi; Imran, Sarojini; Zainab Nasir, Syeda; Desty Ferentya, Marsha; Dwi Amanda, Marcela; Luqiana Nasution, Fairly Ivana (LPPI UMN AL WASHLIYAH, 2024)
This counseling aims to improve the understanding of SMK 2 Wisata Perintis Depok students regarding the dangers of drugs and preventive measures. Methods used include pre-test, post-test, material counseling, and interactive activities such as discussions and ice-breaking. Results show that the average student's understanding increased from 76% to 89% post-counseloring. This indicates the effectiveness of the activities in enhancing students' awareness of drug dangers. This activity underscores the importance of the school's role in combating drug abuse among teenagers.